Fabrication Of Screen Printed Doped Zinc Oxide Thick Film On Metal Substrate As Heat Sink For High Power Light Emitting Diodes - Mah, Jian Wen (2018)
A large amount of heat trapped inside Light Emitting Diode (LED) package is the consequence of large thermal resistance between the heat source and the heat sink. These large thermal resistances created a huge amount of heat accumulated inside the LED package resulting in poorer luminous efficiency, shorter life time, shifting of emission wavelength and reliability issues. Typically, the junction temperature of the LED was found to be approximately 120°C on 250mA of applied forward current. In this project, pure and four different metal-doped ZnO thick films were deposited on Aluminium substrate by screen printing technique using nano-crystalline powder synthesized from co-precipitation method.